Analysis of Factors Influencing Organizational Citizenship Behavior Mediated by Employee Job Satisfaction at PT. BSL, Kedurang Ilir District - Agustina, Dwi (Universitas Bengkulu, 2023)
The purpose of this study was to determine the effect of Emotional Intelligence and Work-Life Balance on Organizational Citizenship Behavior mediated by employee job satisfaction at PT BSL Kedurang Ilir District. The theory used in this study is empathy-altruism theory and affective event theory. The measurement indicators in this study consisted of 38 indicators which were used as instruments to collect sample data from respondents. This research uses a quantitative approach with a research design, namely a survey design. The data used is primary data obtained through direct questionnaire distribution. This research involved employees of PT BSL Kedurang Ilir District. The sampling technique used the census technique. The total sample in this study were 184 respondents. This research data processing technique uses SEM PLS (Partial Least Square) with the help of the Smart PLS version 4.0 program. The tests carried out in this study are outer model, inner model, hypothesis testing and mediation effect testing. The results of this study indicate that: 1) Emotional Intelligence has no significant effect on Organizational Citizenship Behavior. 2) Work-Life Balance has a significant effect on Organizational Citizenship Behavior. 3) Job satisfaction has a significant effect on Organizational Citizenship Behavior. 4) Emotional Intelligence has an insignificant effect on job satisfaction. 5) Work-Life Balance has a significant effect on job satisfaction. 6) Job satisfaction is proven unable to mediate Emotional Intelligence on Organizational Citizenship Behavior. 7) Job satisfaction is proven to be able to mediate Work-Life Balance on Organizational Citizenship Behavior.